PVTx properties of the R600a/R245fa for low temperature organic rankine cycle. (January 2023) - Xu, Wenlin; Qi, Yingxia; Yang, Yushui; Ge, Yinfei; Lu, Yang; Liu, Yefeng; Zhao, Wei
Highlights: The mixed refrigerants (R600a + R245fa) as a new alternative R245fa refrigerant. PVTx experimental data of (R600a + R245fa) mixtures at six mass fractions. Virial equations of state are fitted. Abstract: The gaseous PVTx properties of the mixtures of 2-methylpropane(R600a) + 1, 1, 1, 3, 3-pentafluoropropane(R245fa) are measured by the Burnett isothermal expansion method while the temperatures are 300.2 K to 335.9 K and the corresponding pressures are 144.09 kPa to 895.20 kPa. The mass fraction of R600a ranges from 0.15 to 0.40. The uncertainties of the experimental equipment are estimated as: the temperature uncertainty is ±8.1 mK, the pressure uncertainty is ±1.7 kPa, and the mass fraction uncertainty is ±0.003. The results of the experiment are rectified by the virial equation of state (EOS) and the fitting virial coefficients of the virial EOS are obtained. The pressures obtained by virial EOS agree well with the experimental pressures with the relative deviations within ±0.9 %. This study provides the meaningful information for the further studies on the Organic Rankine Cycle using these novel mixed refrigerants.